1981
DOI: 10.1037/0096-1523.7.2.388
|View full text |Cite
|
Sign up to set email alerts
|

Levels of processing in speech production.

Abstract: When subjects repeated short alphabetic sequences at experimenter-controlled rates while retaining consonant trigrams, subsequent recall was unrelated to speech rate if single letters or a long sequence was repeated, but recall was inversely related to speech rate for sequences three or five letters in length. The latter effect was predicted by a model in which sequences were organized as single response units in a central phonetic processor but independently executed by means of mechanisms not requiring the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…The terminal bend occurred at W (23rd letter) for both conditions, indicating a smaller range of serial search toward the end of the alphabet than at the beginning. This result is remarkably similar to one obtained by Aldridge (1981), where the results suggested that the longest spoken, alphabetic sequence that could be organized into a single utterance was limited by the capacity of STM. Evidence suggested that the maximum stable sequence from the beginning of the alphabet would be A through H but the maximum sequence from the end of the alphabet would be shorter, approximately V through Z.…”
Section: Experiments 1asupporting
confidence: 89%
“…The terminal bend occurred at W (23rd letter) for both conditions, indicating a smaller range of serial search toward the end of the alphabet than at the beginning. This result is remarkably similar to one obtained by Aldridge (1981), where the results suggested that the longest spoken, alphabetic sequence that could be organized into a single utterance was limited by the capacity of STM. Evidence suggested that the maximum stable sequence from the beginning of the alphabet would be A through H but the maximum sequence from the end of the alphabet would be shorter, approximately V through Z.…”
Section: Experiments 1asupporting
confidence: 89%
“…A second reason is that the studies of speech production that have considered attention demands have argued mainly from hesitations and slips of the tongue observed in spontaneous speaking (see Bock, 1982; Clark & Clark, 1977; Dechart & Raupach, 1980; Fodor, Bever, & Garrett, 1974; Foss & Hakes, 1978; Gee & Grosjean, 1983; Goldman-Eisler, 1968; Levin, Silverman, & Ford, 1967). Examination of interference in concurrent task situations has been relatively rare (for exceptions, see Aldridge, 1981; Ford & Holmes, 1978), as have studies of response to stress for speed versus accuracy (see MacKay, 1982). And few, if any, speech production studies have looked at the combined effects of such factors manipulated simultaneously.…”
Section: Discussionmentioning
confidence: 99%